Biaxially oriented polyarylene sulfide film

The two-axis oriented polyphenylene sulfide film addresses heat deformation and transmission loss issues by controlling melting point and crystallinity, providing improved stability and performance for high-frequency circuits.

JP7622433B2Active Publication Date: 2025-01-28TORAY INDUSTRIES INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020562227
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-04
Filing Date
2020-09-02
Publication Date
2025-01-28
Estimated Expiration
2040-09-02

AI Technical Summary

Technical Problem

Existing polyphenylene sulfide (PPS) films used as circuit base materials face issues with heat deformation, warping, and increased transmission loss due to uneven film surfaces, which are exacerbated by low molecular chain stretching and high thermal contraction stress.

Method used

A two-axis oriented polyphenylene sulfide film with controlled melting point, crystallinity, and surface smoothness is developed, using a specific resin composition and manufacturing process to enhance heat dimension stability and processing characteristics.

Benefits of technology

The film exhibits improved heat dimension stability, reduced contraction stress, and enhanced transmission characteristics, making it suitable for high-frequency circuit materials and other applications requiring thermal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622433000001
    Figure 0007622433000001
  • Figure 0007622433000002
    Figure 0007622433000002
  • Figure 0007622433000003
    Figure 0007622433000003
Patent Text Reader

Abstract

The present invention addresses the problem of providing a biaxially oriented polyarylene sulfide film having exceptional thermal dimensional stability, processability, and transmission characteristics. A biaxially oriented polyarylene sulfide film having a structural component composed mainly of a polyarylene sulfide (PAS) resin and having a melting start temperature (Tms) and a melting point (Tm), measured in the first run under conditions of a heating rate of 20°C / min and a sample quantity of 5 mg using differential scanning calorimetry (DSC), that satisfy expression (1). Expression (1): 20°C ≤ Tm - Tms ≤ 100°C
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to biaxially oriented polyarylene sulfide films. [Background technology]

[0002] Polyarylene sulfide films have excellent heat resistance, electrical properties, low moisture absorption, dimensional stability at high temperatures, and chemical resistance, and are therefore ideally used as insulating and heat-insulating materials for electrical and electronic components, battery components, machine parts, and automotive parts.

[0003] In recent years, in the field of electric and electronic components, materials with low transmission loss are required due to the trend toward high speed and large capacity, and circuit boards using liquid crystal polymer films are known as low transmission loss materials (Patent Document 1). However, when liquid crystal polymers are used, there is a problem that the molecular chains have a highly oriented structure and low elongation, making them prone to cracking and insufficient processing. Therefore, polyarylene sulfide films, represented by polyphenylene sulfide (hereinafter sometimes abbreviated as PPS), are being applied to electrical insulating materials by taking advantage of their high transmission loss and low moisture absorption. However, those using PPS films as circuit substrates undergo thermal dimensional changes, and for example, when heat is applied during the manufacturing process of circuit boards, deformation and warping of the circuit is likely to occur. This is because the shrinkage stress caused by heat in PPS films is large, which deforms the circuit layer, and low shrinkage stress of PPS films is desired. In addition, in high frequency band transmission, electrical signals flow through the surface of the circuit, so if the surface unevenness of the film becomes large, the transmission path becomes longer and the amount of transmission loss increases, so a film with excellent surface smoothness is desired. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2011-60449 A [Patent Document 2] WO2007 / 129721 publication [Patent Document 3] JP 2007-301784 A [Patent Document 4] JP 2002-47360 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, therefore, PPS films have been proposed in which a different thermoplastic resin is added to a polyarylene sulfide resin to improve durability and processability in order to improve moldability at high temperatures (Patent Documents 2 and 3). However, although this improves thermoformability, there is a problem in that it does not sufficiently suppress the thermal shrinkage stress during the manufacturing process of the circuit board.

[0006] Furthermore, a technology has been disclosed in which PPS film for use in circuit boards is heated in stages under high pressure to improve its thermal stability (Patent Document 4). However, because the heating is performed in stages and pressure and time are required, which leads to embrittlement of the film, there is an issue that the processability for use as a circuit board is insufficient.

[0007] The present invention has an object to solve the above-mentioned problems, that is, to provide a biaxially oriented polyarylene sulfide film excellent in thermal dimensional stability, processability and transmission properties. [Means for solving the problem]

[0008] The biaxially oriented polyarylene sulfide film of the present invention has the following configuration in order to solve the above problems: That is, the biaxially oriented polyarylene sulfide film contains a polyarylene sulfide resin as a main constituent, and has a melting initiation temperature (Tms) and a melting point (Tm) measured in the first run using differential scanning calorimetry (DSC) at a heating rate of 20°C / min and a sample weight of 5 mg, which satisfy the following formula (i): 20℃≦Tm-Tms≦100℃ (1) Effect of the Invention

[0009] The biaxially oriented polyarylene sulfide film of the present invention has excellent thermal dimensional stability, processability, and transmission characteristics, and can therefore be suitably used for electrical and electronic devices, battery components, machine parts, automotive parts, insulating materials, printing device components, heat-resistant tapes, and particularly high-frequency circuit materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will now be described.

[0011] In the present invention, a biaxially oriented polyarylene sulfide film is a biaxially oriented film obtained by melt-molding a resin composition whose main component is a polyarylene sulfide (hereinafter referred to as "PAS")-based resin into a sheet, biaxially stretching the sheet, and heat treating the sheet.

[0012] In the present invention, the term "mainly composed of PAS resin" means that the PAS resin is contained in an amount of 50% by mass or more, preferably 60% by mass or more, and more preferably 70% by mass or more. If the PAS resin content is less than 50% by mass, the heat resistance, dimensional stability, and mechanical properties, which are characteristics of the PAS film, may be impaired.

[0013] The PAS resin used in the present invention is a copolymer having a repeating unit of -(Ar-S)-, where Ar includes units represented by the following formulae (A) to (K).

[0014] [ka]

[0015] (R1 and R2 are substituents selected from hydrogen, alkyl groups, alkoxy groups, and halogen groups, and R1 and R2 may be the same or different.) As the repeating unit, a p-arylene sulfide unit is preferable, and representative examples thereof include polyphenylene sulfide, polysulfone, polyether sulfone, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, and the like. From the viewpoints of film properties and economic efficiency, a particularly preferable p-arylene sulfide unit is a p-phenylene sulfide unit.

[0016] The polyarylene sulfide resin used in the present invention is preferably composed of p-phenylene sulfide units represented by the following structural formula as the main structural unit in an amount of 80 mol % to 99.9 mol % of all repeating units. By making the composition as described above, excellent heat resistance and chemical resistance can be exhibited.

[0017] [ka]

[0018] In addition, it can also be copolymerized with a copolymerization unit in an amount of 0.01 mol % or more and 20 mol % or less of the repeating unit.

[0019] Preferred copolymer units are

[0020] [ka]

[0021] (wherein X represents an alkylene, CO, or SO2 unit; and R represents an alkyl, nitro, phenylene, or alkoxy group), and a particularly preferred copolymerization unit is the m-phenylene sulfide unit.

[0022] The mode of copolymerization of the main structural unit with the copolymerization component is not particularly limited, but a random copolymer is preferred.

[0023] The molecular weight of the PAS resin constituting the biaxially oriented polyarylene sulfide film of the present invention is preferably 40,000 or more, more preferably 60,000 or more, in terms of weight average molecular weight.

[0024] By setting the molecular weight within the above range, the fluidity in the molten state can be controlled, and the entanglement of molecular chains increases, improving dispersibility when mixed with other thermoplastic resins described later, and increasing surface smoothness. Important If the average molecular weight is less than 40,000, the viscosity of the PAS resin when melted is low. Therefore, the resin extruded from the die cannot be cast stably, which may cause uneven thickness and width fluctuation of the sheet. There is no particular upper limit for the weight average molecular weight, but 110,000 or less is the practical upper limit for a resin that can be stably extruded using general-purpose equipment. The weight average molecular weight can be controlled by the polymerization conditions described later to set it within the above range. The weight average molecular weight can also be measured by gel permeation chromatography (GPC).

[0025] The biaxially oriented polyarylene sulfide film of the present invention is required to have a melting initiation temperature (Tms) and melting point (Tm) measured in the first run using differential scanning calorimetry (DSC) at a heating rate of 20°C / min and a sample weight of 5 mg, which satisfy the following formula (i):

[0026] 20℃≦Tm-Tms≦100℃ (i) The melting initiation temperature (Tms) referred to here means the temperature at which the microcrystals start to melt. The melting point (Tm) means the solid-liquid transition temperature of the resin film. The melting initiation temperature and the melting point are calculated by the method described below from a differential scanning calorimetry chart obtained by heating from 25°C to 350°C (1st Run) under the above-mentioned conditions in accordance with JIS K-7122 (1987). In the present invention, the microcrystals are crystals that start to melt at a low temperature. If a large number of microcrystals are present, dimensional changes may occur even at low temperatures, resulting in poor heat resistance.

[0027] By setting the melting start temperature and melting point within the above range, the microcrystals are reduced. Even when exposed to high temperatures, shrinkage due to melting of the microcrystals can be suppressed. Therefore, a film excellent in thermal dimensional properties and in that the shrinkage stress of the entire film can be reduced and deformation suppressed during processing can be obtained. If the difference between the melting point and the melting start temperature exceeds 100°C, the melting of the microcrystals begins at a low temperature, and the shrinkage stress increases, which may cause film deformation during processing. In addition, if the difference between the melting point and the melting start temperature is less than 20°C, the crystallization of the film tends to progress. Therefore, the film becomes embrittled and cracks or peeling may occur during processing. The difference between the melting point and the melting start temperature is more preferably 30°C or more and 70°C or less, and even more preferably 40°C or more and 60°C or less. In order to set the difference between the melting point and the melting start temperature (Tm-Tms) within the above range, it can be controlled by the heat setting treatment and annealing treatment conditions among the film formation conditions described later.

[0028] The biaxially oriented polyarylene sulfide film of the present invention preferably has a rigid amorphous amount of 40% or more and 55% or less relative to the entire film. The above characteristics mean that the amorphous portion is oriented and thermally stabilized. The circuit board manufacturing process has low shrinkage stress, small thermal dimensional change, and good characteristics. If the rigid amorphous amount is less than 40%, the crystallinity in the film increases, and cracks, burrs, etc. may occur during processing. If the rigid amorphous amount exceeds 55%, the crystallinity of the entire film decreases, so that the shrinkage stress increases and the thermal dimensional stability may deteriorate. A more preferred rigid amorphous amount is 40% or more and 50% or less. In order to set the rigid amorphous amount in the above range, it can be controlled by the annealing conditions among the film formation conditions described later. The rigid amorphous amount can be evaluated by the method described later.

[0029] The biaxially oriented polyarylene sulfide film of the present invention preferably has a crystallinity of 25% or more and 45% or less, more preferably 30% or more and 38% or less. By having the above characteristics, the film can be moderately crystallized, and the film can have both heat resistance and processability, and can have good characteristics. If the crystallinity is less than 25%, the crystallinity of the entire film decreases, so that the shrinkage stress increases and the thermal dimensional stability may deteriorate. In addition, if the crystallinity exceeds 45%, the crystallinity of the entire film increases, and the film may become embrittled during processing, resulting in cracks, burrs, etc. In order to set the crystallinity within the above range, it can be controlled by the heat treatment conditions among the film formation conditions described later. The crystallinity can be evaluated by the thermal analysis method described later.

[0030] The biaxially oriented polyarylene sulfide film of the present invention preferably has a ratio of the rigid amorphous amount to the entire film greater than the crystallinity. By having the above characteristics, the rigid amorphous amount suppresses the embrittlement of the film, while the crystallinity balances the thermal dimensional stability and processability, resulting in good characteristics. When the crystallinity ratio increases, the thermal dimensional stability increases, but the processability may deteriorate. In order to make the rigid amorphous amount greater than the crystallinity, it is preferable to adjust the annealing conditions among the film-forming conditions described below.

[0031] The biaxially oriented polyarylene sulfide film of the present invention preferably has a shrinkage stress onset temperature of 220°C or higher, as measured by thermomechanical analysis (TMA). More preferably, it is 230°C or higher, and even more preferably, it is 240°C or higher. In the present invention, the shrinkage stress onset temperature refers to the temperature at which the shrinkage stress begins to increase rapidly when a temperature-shrinkage stress curve is drawn with temperature on the horizontal axis and shrinkage stress on the vertical axis. The shrinkage stress onset temperature indicates that deformation due to shrinkage is small up to that temperature. By having the above characteristics, deformation due to shrinkage can be suppressed, and therefore the film has a good thermal dimensional stability. If the temperature is less than 220°C, deformation due to shrinkage occurs from a low temperature, and the thermal dimensional stability may deteriorate. In order to set the onset of the shrinkage stress within the above range, the annealing temperature can be controlled among the film-forming conditions described later.

[0032] The biaxially oriented polyarylene sulfide film of the present invention preferably has a shrinkage stress of 3.0 MPa or less at 250°C. More preferably, it is 2.0 MPa or less, even more preferably, it is 1.5 MPa or less, and most preferably, it is 1.0 MPa or less. By having the above characteristics, it is possible to suppress thermal deformation during processing, and the residual stress when combined with other members and processed is small, so that it has a good thermal dimensional stability. If it exceeds 3.0 MPa, the shrinkage and residual stress during processing will be large, and the thermal dimensional stability may be deteriorated. The shrinkage stress can be set to the above range by controlling the heat setting temperature and annealing conditions among the film formation conditions described later.

[0033] The biaxially oriented polyarylene sulfide film of the present invention is mainly composed of a PAS resin (I) and contains at least one thermoplastic resin (II) different from the PAS resin (I), and the thermoplastic resin (II) contains at least one structure of the following chemical formulas, more preferably at least one of the structures, including chemical formulas (A), (B), (C) and (D), and more preferably chemical formulas (A) and (D). In particular, when the chemical formula (A) is contained, it is preferable because it contributes to high thermal dimensional stability, processability, and improvement of film formability (particularly stretchability) due to reduction of shrinkage stress, and this is presumed to be due to the interaction between the thermoplastic resin (B) containing the chemical formula (A) and the PAS resin. Note that, when the thermoplastic resin (I) does not contain the structure of the following chemical formula, not only is sufficient thermal dimensional stability and processability not obtained, but also peeling occurs at the interface with the thermoplastic resin B when the resin kneaded with the PAS resin is made into a film and stretched, which may lead to breakage of the film, which is not preferable.

[0034] [ka]

[0035] (In the formula, R1 to R6 each represent a hydrogen atom, a hydroxyl group, a methoxy group, an ethoxy group, a trifluoromethyl group, an aliphatic group having 1 to 13 carbon atoms, or an aromatic group having 6 to 10 carbon atoms.) As the thermoplastic resin (B), for example, various polymers such as polyamide, polyetherimide, polyethersulfone, polyphenylsulfone, polysulfone, polyphenylene ether, polyester, polyarylate, polyamideimide, polycarbonate, polyetheretherketone, etc., and blends containing at least one of these polymers can be used. From the viewpoint of heat resistance and electrical insulation, the thermoplastic resin (B) is more preferably a resin selected from polyphenylsulfone, polyphenylene ether, polysulfone, and polyetherimide. Polyphenylsulfone is even more preferable.

[0036] In the present invention, the timing of mixing the PAS resin (I) and the thermoplastic resin (II) is not particularly limited. There are methods in which the mixture of the PAS resin (I) and the thermoplastic resin (II) is pre-melted and kneaded before melt extrusion, and then pelletized to form a master pellet, and methods in which the mixture is mixed and melt kneaded during melt extrusion. Among them, a method of forming a master pellet using a device that applies shear stress, such as a twin-screw extruder, is preferred. In this case, it is preferred to knead in the kneading section so that the resin temperature is in the range of 5°C to 80°C relative to the melting point of the PAS resin (I). More preferably, the temperature is in the range of 10°C to 80°C relative to the melting point of the PAS resin (I), and even more preferably, the temperature is in the range of 15°C to 70°C. In addition, it is preferred to set the screw rotation speed in the range of 100 rpm to 1500 rpm. By setting the resin temperature and the screw rotation speed in the preferred range, the dispersion diameter of the dispersed phase can be controlled. The ratio of (screw shaft length / screw shaft diameter) of the twin-screw extruder is preferably in the range of 20 or more and 60 or less, and more preferably in the range of 30 or more and 50 or less.

[0037] In the biaxially oriented polyarylene sulfide film of the present invention, it is preferable that the thermoplastic resin (II) exists as a dispersed phase in the PAS resin (I). The dispersed phase here refers to the island components of the sea-island structure constituted by the PAS resin (I) and the thermoplastic resin (II). The island components mean that the thermoplastic resin (II) exists in the biaxially oriented polyarylene sulfide film of the present invention in a state such as a circular, elliptical, spindle-shaped, or amorphous form. The cross section of the film of the present invention can be observed with a transmission electron microscope (TEM) or a scanning electron microscope (SEM) to confirm its morphology.

[0038] The thermoplastic resin (B) contained in the biaxially oriented polyarylene sulfide film of the present invention preferably has a sulfonyl group. If it does not contain a sulfonyl group, it may not have affinity with the PAS resin and may not be able to suppress the formation of microcrystals.

[0039] The biaxially oriented polyarylene sulfide film of the present invention has a PAS resin (I) content W I and the content W of thermoplastic resin (II) different from PAS resin (I). II When the total of the above is taken as 100 parts by weight, the content W of the thermoplastic resin (II) is II is preferably 0.1 parts by weight or more and less than 50 parts by weight. More preferably, the content W II is 0.1 parts by weight or more and less than 30 parts by weight, and more preferably the content W II is 0.1 parts by weight or more and less than 15 parts by weight. If the content of the thermoplastic resin (II) is 50 parts by weight or more, there is a risk that frequent breakage occurs during stretching, making it impossible to stably form a film. II If the amount is less than 0.1 part by weight, the thermal dimensional stability may decrease.

[0040] The biaxially oriented polyarylene sulfide film of the present invention preferably has a center plane average roughness (SRa) of at least one surface of 15 nm or more and 300 nm or less. SRa is a parameter of three-dimensional surface roughness, and means the average roughness at the center plane when the surface roughness curve is approximated by a sine curve, and is defined as the center plane average roughness. The center plane average roughness is a three-dimensional extension of the center line average roughness (Ra) of the two-dimensional roughness parameter described in JIS-B0601-1994, and is obtained by dividing the volume of the part surrounded by the surface shape curved surface and the center plane by the measured area. When the center plane is the XY plane, the vertical direction is the Z axis, and the measured surface shape curve is f(x, y), it is defined by the following formula (ii). Here, Lx is the measured length in the X direction, and Ly is the measured length in the Y direction.

[0041]

number

[0042] By setting the SRa within the above range, when a metal foil (e.g., copper) is laminated directly or via an adhesive to form a circuit, the transfer of unevenness to the copper foil can be reduced, and the transmission characteristics can be improved. If the SRa is less than 15 nm, the slipperiness deteriorates during the conveying process during film formation, and fine scratches may occur on the surface, resulting in uneven characteristics after circuitization. If the SRa exceeds 300 nm, the surface unevenness may be large, and the transmission characteristics may deteriorate. The SRa is preferably 30 nm or more and 200 nm or less, and more preferably 50 nm or more and 150 nm or less. When the PAS resin is kneaded with another thermoplastic resin, the molecular weight of the PAS resin can be changed to control the dispersion diameter, and the surface roughness can be controlled by the dispersion diameter. The surface roughness can be evaluated using a surface roughness meter described later.

[0043] The biaxially oriented film in the present invention refers to a biaxially stretched film, and can be judged by the orientation parameter (Q) measured by a molecular orientation meter being 3700 or more. The orientation parameter (Q) is more preferably 4200 or more. In the case of an unstretched film or a uniaxially stretched film, the orientation of the molecular chains may be insufficient, and the microcrystals may be controlled, resulting in poor thermal dimensional stability, or crystallization due to heat may be promoted, resulting in poor processability. There is no particular upper limit for the value of the orientation parameter (Q), but a practical upper limit is 5500 or less as a film that can be stably formed without breakage.

[0044] The method for producing the biaxially oriented polyarylene sulfide film of the present invention will be described using an example of a film production method in which polyphenylene sulfide resin (hereinafter sometimes abbreviated as PPS resin) is used as the polyarylene sulfide-based resin and polyphenylsulfone resin is used as the other thermoplastic resin. The present invention is not limited to this example.

[0045] First, the manufacture of PPS resin will be described. The following explanation is an example. Sodium sulfide and p-dichlorobenzene are mixed and reacted in an amide-based polar solvent such as N-methyl-2-pyrrolidone (NMP) under high temperature and pressure. If necessary, it is also possible to include copolymerization components such as m-dichlorobenzene and trihalobenzene. Potassium hydroxide, alkali metal carboxylate, etc. are added as a polymerization degree regulator and the polymerization reaction is carried out at 230 to 290°C. After polymerization, the polymer is cooled, and the polymer is made into a water slurry and filtered through a filter to obtain a wet granular polymer.

[0046] An amide-based polar solvent is added to this granular polymer, which is then stirred and washed at a temperature of 30-100°C, washed several times with ion-exchanged water at 30-80°C, washed several times with an aqueous solution of a metal salt such as calcium acetate, and then dried to obtain a granular polymer of polyphenylene sulfide. This granular polymer is fed into a vented extruder and melt-extruded into a strand, cooled with water at a temperature of 25°C, and then cut into chips to produce PPS chips.

[0047] The obtained PPS granular polymer is pre-melted and kneaded (pelletized) with polyphenylsulfone resin under the above-mentioned conditions to prepare a master chip. In the production of the film of the present invention, first, PPS chips are prepared by drying under reduced pressure at 180° C. for 3 hours. PPS and a master batch are mixed in a predetermined ratio, fed to a full-flight single-screw extruder with a melting section set at 300 to 350° C., passed through a filter, and then extruded from a T-die type nozzle, and brought into close contact with a cooling drum with a surface temperature of 20 to 70° C. while applying a static charge thereto, for rapid solidification, to obtain an unstretched film in a substantially unoriented state.

[0048] Next, for biaxial stretching, the unstretched film obtained above is biaxially stretched in the range of the glass transition temperature (Tg) or higher and the cold crystallization temperature (Tcc) or lower of the polyarylene sulfide resin using a sequential biaxial stretching machine or a simultaneous biaxial stretching machine, and then a one-stage or multi-stage heat treatment is performed at a temperature in the range of 150 to 280° C. to obtain a biaxially oriented film. As the stretching method, a sequential biaxial stretching method (a stretching method in which stretching in one direction at a time is combined, such as a method in which stretching in the longitudinal direction is performed followed by stretching in the transverse direction), a simultaneous biaxial stretching method (a method in which stretching in the longitudinal direction and the transverse direction is performed simultaneously), or a combination of these methods can be used.

[0049] Here, a sequential biaxial stretching method is exemplified in which stretching is first performed in the longitudinal direction and then in the transverse direction.

[0050] The unstretched film is heated by a group of heating rolls and stretched in the longitudinal direction (MD) by 2.0 to 4.0 times, more preferably 2.3 to 3.3 times, in one stage or in two or more stages (MD stretching). The stretching temperature is in the range of Tg to Tcc, preferably (Tg+5) to (Tcc-10)°C. Then, it is cooled by a group of cooling rolls at 20 to 50°C.

[0051] As a method of stretching in the width direction, i.e., the TD direction, following the MD stretching, for example, a method using a tenter is common. Both ends of the film are held with clips and introduced into the tenter, where the film is stretched in the width direction. This is called TD stretching. The stretching temperature is preferably in the range of Tg to Tcc, more preferably in the range of (Tg+5) to (Tcc-10)°C. From the viewpoint of the flatness of the film, the stretching ratio is preferably 3.0 to 5.0 times, and more preferably 3.0 to 4.5 times.

[0052] In this case, the ratio of the MD magnification to the TD magnification (stretching magnification ratio=MD magnification / TD magnification) of the film is preferably 1.0 or less, more preferably 0.9 or less, and more preferably 0.80 or less from the viewpoint of improving thermal dimensional stability.

[0053] In the present invention, it is preferable to carry out the heat setting after stretching in two or more steps with different temperatures in a stepwise manner. By carrying out the above heat setting treatment, it is possible to control the crystal formation by heat treatment, to produce uniform crystals, and to improve the thermal dimensional stability, which is preferable. As for the heat setting temperature, it is preferable that the heat setting temperature Ths1 (°C) of the first stage is 180°C to Tm, and the heat setting temperature Ths2 (°C) of the final stage is 230°C to Tm°C.

[0054] In the present invention, the "first stage" refers to a step excluding the final stage of a heat setting process carried out in two or more stages. For example, in a case where the heat setting process is composed of three stages, the first and second stages correspond to the first stage, and the third stage corresponds to the final stage.

[0055] When the heat setting temperature (Ths1) of the previous stage is set in the above range, it is preferable because it is a temperature at which crystallization is easily promoted and orientation relaxation does not easily proceed, so that small-sized microcrystals can be uniformly produced from the precursor of the crystal structure. By producing uniform microcrystals, it is preferable because the crystals can be effectively melted in the annealing treatment described below, and the relaxation treatment can be promoted. Specifically, as described above, it is preferable that the temperature is 180 to Tm°C, and more preferably 200 to Tm°C. It is preferable that the heat setting temperature of the final stage (hereinafter sometimes abbreviated as Ths2) is set to a temperature between Ths1 and the melting temperature (Tm), because it is possible to grow crystals from the crystal nuclei formed in the previous stage as base points, forming uniform crystals and reducing shrinkage stress.

[0056] The heat setting temperature (Ths1) is preferably 230 to 280°C, more preferably 250 to 280°C. When the heat setting treatment of the present invention is carried out in three or more stages, the heat setting temperature is preferably gradually increased from the first stage to the second stage to the third stage within the above-mentioned preferred temperature ranges of Ths1 and Ths2. The heat setting time is preferably 1 second to 1000 seconds for each heat setting stage in the preceding stages, more preferably 1 second to 60 seconds, and even more preferably 1 second to 30 seconds. The heat setting time in the final stage is preferably 1 second to 1000 seconds, more preferably 1 second to 60 seconds, and even more preferably 1 second to 10 seconds. The total heat setting time is preferably not more than 2000 seconds, more preferably 120 seconds, even more preferably 30 seconds, and particularly preferably not more than 20 seconds. In the present invention, the heat setting treatment process is preferably a process of two or more stages, but in consideration of the total heat setting time, it is more preferable that it is two or more stages and not more than three stages.

[0057] Furthermore, before subjecting this film to a cooling step, it is preferable to subject it to a relaxation treatment in the width direction at a temperature of not less than the stretching temperature and not more than Ths2 (°C). The relaxation rate is the ratio of the difference between the width before treatment and the width after treatment, and for example, a relaxation rate of 2% indicates that if the width before treatment is 100 mm, then the width after treatment is 98 mm after relaxation of 2% (2 mm). Rxhs is preferably 0 to 9%.

[0058] Thereafter, after cooling, preferably to a temperature below 35° C., more preferably below 25° C., the film edges are removed and wound onto a core.

[0059] Furthermore, the wound biaxially oriented PPS film is preferably conveyed under tension under a certain temperature condition, and is preferably annealed to improve thermal dimensional stability for the purpose of further homogenizing the crystals. The annealing temperature (hereinafter sometimes abbreviated as Ta) is preferably a temperature of Ths1 or more and Ths2 or less (°C), more preferably more than 230°C and less than 270°C. If it exceeds 270°C, it relaxes even the structure fixed by the heat setting treatment, causing recrystallization and deteriorating processability. If it is less than 230°C, the removal of distortion in the molecular structure by the annealing treatment is incomplete, and the heat shrinkage stress in the high temperature range remains, which may deteriorate the thermal dimensional stability.

[0060] The annealing time is preferably 1 to 300 seconds, more preferably 30 to 150 seconds. In addition, in the annealing treatment, it is preferable to control the temperature in the winding process after the annealing treatment. The winding temperature after the annealing treatment is preferably Tg+20°C or less. If it exceeds Tg+20°C, the heat applied during the annealing treatment remains in the winding process, and the winding tension may cause orientation and microcrystals to form, resulting in poor thermal dimensional stability. The winding temperature after the annealing treatment is preferably Tg or less. The winding temperature after the annealing treatment may be reduced at the outlet by providing a stepwise temperature difference in the annealing oven, by contacting the annealing oven outlet with a cooling roll, or by cooling with air at the annealing oven outlet. Any of these methods may be used, and among them, the air cooling method at the annealing oven outlet is preferable from the viewpoint of productivity. The biaxially oriented PPS film of the present invention can be obtained by annealing the film while transporting it at a speed of 1 to 100 m / min.

[0061] In the present invention, the biaxially oriented polyarylene sulfide film or its film roll may be subjected to any processing such as molding, surface treatment, lamination, coating, printing, embossing, and etching, if necessary.

[0062] The biaxially oriented polyarylene sulfide film of the present invention has excellent thermal dimensional stability, processability, and transmission characteristics, and can therefore be suitably used as various parts for automobiles and electric and electronic materials, heat-resistant tape substrates, films for printing toner stirrers, release films, and particularly high-frequency circuit substrates.

[0063] [Method of measuring characteristics] (1) Melting point (Tm), melting temperature (Tms) The film was measured in accordance with JIS K-7121 (1987) and JIS K-7122 (1987) using a differential scanning calorimeter "ROBOT DSC-RDC220" manufactured by Seiko Denshi Kogyo Co., Ltd. as the measuring device and Disk Session "SSC / 5200" for data analysis, as follows.

[0064] 5 mg of film sample was weighed into a sample pan, and the resin was heated from 25°C to 350°C at a temperature increase rate of 20°C / min (1st run) to obtain a differential scanning calorimeter chart. The peak temperature of the endothermic peak of melting observed at that time was measured. (a) Melting point (℃) From the differential scanning calorimetry chart obtained as described above, the temperature of the endothermic peak of melting observed is measured. If two or more peaks are observed, the peak temperature of the endothermic peak on the highest temperature side is taken as the melting point. The measurement is carried out three times for each sample, and the average value of the obtained values ​​is taken as the melting point (°C) of the sample. (b) Melting temperature (℃) From the differential scanning calorimetry chart obtained above, the temperature at which the endothermic peak of the melting point ends is taken as Tmend, and the straight line connecting Tmend+5°C and Tmend+25°C is taken as the baseline, which is extended to the lower temperature side. The intersection of this baseline and the differential scanning calorimetry chart is taken as the melting start temperature. Measurements were performed three times for each sample, and the average of the obtained values ​​was taken as the melting start temperature (°C) of the sample.

[0065] (2) Rigid amorphous amount (%), crystallinity (%) (A) Movable amorphous amount (%) Using a TA Instruments temperature modulated DSC (Q1000), 5 mg of sample was measured in a nitrogen atmosphere from 0 to 250°C at a heating rate of 2°C / min, a temperature modulation range of ±1°C, and a temperature modulation period of 60 seconds. The glass transition temperature (Tg) and the specific heat difference (ΔCp) before and after Tg were obtained, and the mobile amorphous amount (Xma) was calculated using the following formula. Movable amorphous amount: Xma(%)=ΔCp / ΔCp 0 ×100 Here, ΔCp 0 represents the difference in specific heat before and after the Tg of completely amorphous PPS, and ΔCp 0 =0.2699J / g℃(Wunderlich B., Thermal Analysis of Polymeric Materials,Appendix 1 (The ATHAS Data Bank),Springer (2005).) is used.

[0066] (B) Crystallinity (%) The crystallinity of the film is calculated using the following formula, taking the endothermic peak observed in the DSC chart of the above-mentioned first run as the crystallization peak. Crystallinity (%) = (endothermic peak heat associated with crystal melting ΔHm - exothermic peak heat associated with crystal formation ΔHc) / heat of fusion ΔHm of completely crystalline polyarylene sulfide 0 ×100 Here, ΔHm when polyarylene sulfide is PPS 0The literature value of 146.44 J / g (Maemura E., Cakmak M., White JL, Polym. Eng. Sci, 29, 140 (1989)) is used.

[0067] (C) Rigid amorphous amount (%) The rigid amorphous amount (Xrigid) was calculated from the mobile amorphous amount (Xma) and crystallinity (Xc) obtained by measurement according to the following formula. Rigid amorphous amount: Xrigid(%)=100 -(Xc+Xma) (3) Shrinkage stress starting temperature, shrinkage stress The measurements were carried out using a thermomechanical measuring device TMA / SS6600 (manufactured by Seiko Instruments Inc.) according to the following procedure. The film was cut into strips 20 mm in the measurement direction and 4 mm in the direction perpendicular to the measurement direction, and the shrinkage force generated when heated from room temperature to 270°C at a heating rate of 10°C / min under constant tensile length conditions was measured.

[0068] (a) Onset temperature of shrinkage stress The temperature at which the shrinkage stress starts to increase rapidly from the temperature-shrinkage stress curve is defined as the starting temperature of the shrinkage stress. In the present invention, the shrinkage stress from 30°C to 80°C is defined as the baseline from the temperature-shrinkage stress curve, and the temperature at which the shrinkage stress starts to increase from the baseline is read and defined as the starting temperature of the shrinkage stress.

[0069] (b) Shrinkage stress The shrinkage stress at 250° C. obtained by the above-mentioned measurement was defined as the shrinkage stress of the present invention.

[0070] (4) Surface roughness The average center line roughness (SRa) of the surface of layer A was determined under the following conditions using a Surfcorder ET30HK manufactured by Kosaka Laboratory.

[0071] Stylus curvature radius: 2μm Cutoff: 0.25mm Measurement length: 0.5mm Measurement interval: 5μm Number of measurements: 40.

[0072] (5) Degree of orientation (Q) The film was cut into a 5 cm x 5 cm square and measured using a molecular orientation meter (MOA-7015, manufactured by Oji Scientific Instruments Co., Ltd.), and the average value of the minimum and maximum values ​​of the degree of orientation (Q) was used as the value.

[0073] (6) Weight average molecular weight The molecular weights of the PPS resin and PPS film were calculated in terms of polystyrene using gel permeation chromatography (GPC), a type of size exclusion chromatography (SEC). The GPC measurement conditions are as follows: Equipment: Senshu Science SSC-7100 Column name: Senshu Kagaku GPC3506 Eluent: 1-chloronaphthalene Detector: Differential refractive index detector Column temperature: 210℃ Pre-thermostat temperature: 250℃ Pump thermostatic chamber temperature: 50℃ Detector temperature: 210℃ Flow rate: 1.0mL / min Sample injection volume: 300 μL (slurry: approximately 0.2% by weight).

[0074] (7) Thermal dimensional stability (a) Thermal dimensional stability (I) After applying circuit board adhesive AW-32 (Kyodo Yakuhin Co., Ltd.) to both surfaces of the biaxially oriented polyarylene sulfide film to a solidified thickness of 2 μm, 12 μm copper foil (3EC-HTE, Mitsui Kinzoku Kogyo Co., Ltd.) was pressed at a pressure of 4 MPa for 10 minutes with a vacuum hot press machine heated to 170 ° C. to laminate it on both surfaces, and a laminate of copper foil / biaxially oriented polyarylene sulfide film / copper foil was produced. A circuit was formed in the obtained laminate by a chemical etching method so that the line length was 100 mm and the characteristic impedance was 50 Ω in a microstrip structure. The circuit was cut out to a length of 110 mm and a width of 5 mm, which is a size including the microstrip line, and the sample was placed on a glass epoxy board with a thickness of 2 mm and treated in a reflow furnace set to an ultimate temperature of 250 ° C. for a treatment time of 5 minutes. The lifting of both ends of the sample before and after treatment was measured, and the average value was taken as the curl amount and judged according to the following criteria. Curl amount (mm) = (Curl amount after processing (mm)) - (Curl amount before processing (mm)) AA: Curl amount is 5mm or less A: Curl amount is 10mm or less B: Curl amount exceeds 10mm and is 20mm or less C: Over 20mm (b) Thermal dimensional stability (II) A circuit was formed on one side of the above-mentioned copper foil / biaxially oriented polyarylene sulfide film / copper foil laminate with a line width of 200 μm, a line length of 100 mm, 11 lines, and a space width of 100 μm. Then, a coverlay film manufactured by Nikkan Industries (Nikaflex CKSE, base film thickness 12.5 μm) was used on both sides and pressed at a pressure of 4 MPa for 90 minutes in a vacuum press device heated to 160°C to laminate it to both surfaces of the circuit laminate, producing a circuit board with a coverlay film bonded to both sides. The circuit board was placed on a 2 mm thick glass epoxy substrate and reflow treatment was performed five times in a reflow furnace set to a final temperature of 250° C., with each treatment time being set to 5 minutes. The processed circuit board was cross-sectioned using a microtome, and the space width was measured at 10 points using a microscope. The average value was taken as the space width deviation and was judged according to the following criteria. Space width deviation (%) = {(average space width after processing (μm)) - (design space width 100 μm)} / (design space width 100 μm) x 100 AA: Space width deviation is between -5% and 5% A: Space width deviation is between -8% and 8% B: Space width deviation is between -10% and 10% C: Space width deviation is between -15% and 15% D: The deviation of the space width is less than -15% and more than 15%.

[0075] (8) Processability Copper foil was laminated on both sides of the biaxially oriented polyarylene sulfide film by the above-mentioned method to prepare a laminate. In order to evaluate the processability of the laminate as a model, a through hole was formed at a laser wavelength of 355 nm using a UV-YAG laser (ESI MODEL5335). The laminate was cut so as to pass through the center of the formed through hole, and observed using an electron microscope and judged according to the following criteria. AA: No burrs or copper foil interface peeling. A: There is some burr, but the copper foil interface is not peeled off. B: Many burrs are generated, but there is no peeling at the copper foil interface. C: Burrs are generated and peeling occurs at the copper foil interface.

[0076] (9) Transmission characteristics Using the above-mentioned method, a microstrip line was formed and used as a sample for evaluation. The obtained sample was left for 24 hours in an environment with a temperature of 23°C and a humidity of 65% RH, and immediately after that, the transmission loss (dB / 100 mm) from 10 to 65 GHz was measured using a network analyzer (Agilent Technology's "8722ES") and a Cascade Microtec probe (ACP40-250). The absolute value of the transmission loss from the value at 60 GHz was used to evaluate the sample according to the following criteria. A: The absolute value of transmission loss is less than 15 dB / 100 mm B: The absolute value of transmission loss is 15 dB / 100 mm or more and less than 20 dB / 100 mm. C: Absolute transmission loss is 20dB / 100mm or more EXAMPLES

[0077] (Reference Example 1) Preparation of polyphenylene sulfide resin granules 1 (PPS granules 1) A 1-liter autoclave equipped with a process stirrer was charged with 1.00 mol of 47% sodium hydrosulfide, 1.03 mol of 96% sodium hydroxide, 1.65 mol of N-methyl-2-pyrrolidone (NMP), 0.45 mol of sodium acetate, and 150 g of ion-exchanged water, and the mixture was gradually heated to 225°C over about 3 hours while stirring at 240 rpm and passing nitrogen through at normal pressure. After distilling off 211 g of water and 4 g of NMP, the reaction vessel was cooled to 160°C. Next, 1.00 mole of p-dichlorobenzene (p-DCB) and 1.31 mole of NMP were added. The reaction vessel was then sealed under nitrogen gas. While stirring at 240 rpm, the temperature was increased from 200°C to 235°C at a rate of 0.6°C / min. After reaching 235°C, the reaction was continued at 235°C for 95 minutes. The temperature was then increased to 270°C at a rate of 0.8°C / min and held for 100 minutes.

[0078] After reaching 270°C, 1 mole of water was injected into the system over 15 minutes. After 100 minutes at 270°C, the mixture was cooled to 200°C at a rate of 1.0°C / min, and then rapidly cooled to near room temperature. The contents were removed, diluted with 0.4 liters of NMP, stirred at 85°C for 30 minutes, and then the solvent and solids were filtered off using an 80 mesh sieve. Following the post-treatment process, 0.5 liters of NMP was added to the obtained solids, stirred at 85°C for 30 minutes, and filtered off.

[0079] The solid matter obtained was washed three times with 0.9 liters of warm water and filtered. The particles obtained were further washed twice with 1 liter of warm water and filtered to obtain polymer particles. These were then dried with hot air at 80°C and then dried under reduced pressure at 120°C. As a result, polyphenylene sulfide (PPS) resin granules (PPS granules 1) with a melting point of 280°C and a weight average molecular weight of 70,000 were obtained.

[0080] (Reference Example 2) Preparation of polyphenylene sulfide resin granules 2 (PPS granules 2) A 1-liter autoclave equipped with a process stirrer was charged with 1.00 mol of 47% sodium hydrosulfide, 1.02 mol of 96% sodium hydroxide, 1.65 mol of N-methyl-2-pyrrolidone (NMP), 0.33 mol of sodium acetate, and 150 g of ion-exchanged water. The mixture was gradually heated to 235°C over about 3 hours while stirring at 240 rpm and passing nitrogen through at normal pressure. After distilling off 211 g of water and 2 g of NMP, the reaction vessel was cooled to 160°C. Next, 1.00 mole of p-dichlorobenzene (p-DCB) and 1.30 mole of NMP were added. The reaction vessel was then sealed under nitrogen gas. While stirring at 400 rpm, the temperature was raised from 200°C to 270°C at a rate of 0.6°C / min, and after reaching 270°C, the reaction was continued at 270°C for 140 minutes. Then, it was cooled from 270°C to 250°C over 15 minutes. At this stage, the amount of water in the system per mole of sulfur component of the charged sulfidizing agent was 1.1 moles. Next, it was cooled from 250°C to 220°C at an average cooling rate of 0.4°C / min. After reaching 220°C, it was rapidly cooled to near room temperature. The contents were removed, diluted with 0.4 liters of NMP, stirred at 85°C for 30 minutes, and then the solvent and solids were filtered off with a sieve (80 mesh). After the post-treatment step, 0.5 liters of NMP was added to the obtained solid, which was stirred at 85°C for 30 minutes and filtered. The obtained solid was washed three times with 0.9 liters of warm water and filtered. The obtained particles were further washed twice with 1 liter of warm water and filtered to obtain polymer particles. These were then dried with hot air at 80°C and dried under reduced pressure at 120°C to obtain polyphenylene sulfide (PPS) resin granules (PPS granules 2) with a melting point of 280°C and a weight average molecular weight of 50,000.

[0081] (Reference Example 3) Preparation of film raw material (PPS1) The PPS granules 1 prepared in Reference Example 1 were fed into a vented co-rotating twin-screw kneading extruder (manufactured by Japan Steel Works, Ltd., screw diameter 30 mm, screw length / screw diameter = 45.5) heated to 320°C, melt-extruded at a residence time of 90 seconds and a screw rotation speed of 150 rpm, discharged in the form of strands, cooled with water at a temperature of 25°C, and immediately cut into chips to prepare a film raw material (PPS1).

[0082] (Reference Example 4) Preparation of film raw material (PPS2) The PPS granules 2 produced in Reference Example 2 were fed into a vented co-rotating twin-screw kneading extruder (manufactured by Japan Steel Works, Ltd., screw diameter 30 mm, screw length / screw diameter = 45.5) heated to 320°C, melt-extruded at a residence time of 90 seconds and a screw rotation speed of 150 rpm, discharged in the form of strands, cooled with water at a temperature of 25°C, and immediately cut into chips to prepare a film raw material (PPS2).

[0083] (Reference Example 5) Preparation of master pellets (MB1) of PPS granules 1 and thermoplastic resin. A co-rotating, vented twin-screw kneading extruder equipped with one kneading paddle kneading section was heated to 320°C. 80 parts by mass of PPS granules 1 obtained in Reference Example 1 and 20 parts by mass of polyphenylsulfone (PPSU: Solvay Advanced Polymers K.K., Radel R5600-NT) were fed from the feed port, and the mixture was melt-kneaded at a screw rotation speed of 250 rpm, discharged in the form of a strand, cooled with water at a temperature of 25°C, and immediately cut to prepare master pellets containing 20 parts by mass of PPSU.

[0084] (Reference Example 6) Preparation of master pellets (MB2) of PPS granules 2 and thermoplastic resin. A co-rotating, vented twin-screw kneading extruder equipped with one kneading paddle kneading section was heated to 320°C, and 80 parts by mass of the PPS granules 2 obtained in Reference Example 2 and 20 parts by mass of polyphenylsulfone (PPSU: Solvay Advanced Polymers K.K., Radel R5600-NT) were fed from the feed port, and the mixture was melt-kneaded at a screw rotation speed of 250 rpm, discharged in the form of a strand, cooled with water at a temperature of 25°C, and immediately cut to prepare master pellets containing 20 parts by mass of PPSU.

[0085] (Reference Example 7) Preparation of master pellets (MB3) of PPS granules 1 and thermoplastic resin. A co-rotating, vented twin-screw kneading extruder equipped with one kneading paddle kneading section was heated to 320°C, and 80 parts by mass of the PPS granules 1 obtained in Reference Example 1 and 20 parts by mass of polyethersulfone (PES: Solvay Advanced Polymers K.K., Veradel 3600) were fed from the feed port, and the mixture was melt-kneaded at a screw rotation speed of 250 rpm, discharged in the form of a strand, cooled with water at a temperature of 25°C, and immediately cut to prepare master pellets containing 20 parts by mass of PES.

[0086] Example 1 75 parts by mass of PPS1 obtained in Reference Example 3 and 25 parts by mass of MB1 obtained in Reference Example 5 were dry-blended, and then vacuum-dried at 180°C for 3 hours. The mixture was then fed to an extruder, melted at 320°C under a nitrogen atmosphere, and introduced into a T-die die. The mixture was then extruded into a sheet form from the T-die die to form a molten monolayer sheet, and the molten monolayer sheet was cast onto a cast drum rotating at 3.0 m / min and maintained at a surface temperature of 25°C while being cooled and solidified by an electrostatic application method to obtain an unstretched film. The unstretched film obtained was stretched at a stretching temperature of 103°C in the longitudinal direction of the film at a ratio of 2.7 times using a longitudinal stretching machine consisting of a plurality of heated rolls, utilizing the difference in peripheral speed of the rolls. Thereafter, both ends of the film were supported by clips, and the film was introduced into a tenter and stretched at a stretching temperature of 100°C in the width direction of the film at a ratio of 3.6 times. Subsequently, the film was heat-treated at 280°C, then 2% relaxation treatment was performed, and the film was cooled to room temperature, after which the film edges were removed to obtain a polyarylene sulfide film with a thickness of 50 μm. The obtained film was then annealed for 130 seconds while being conveyed into an oven heated to 250°C, and cooled with air between the oven exit and the winding roll, and the film was wound up at a winding temperature of 60°C to obtain a biaxially oriented polyarylene sulfide film. The physical properties and characteristics of the obtained film are shown in Table 1.

[0087] Example 2 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except for using PPS2 obtained in Reference Example 4 and MB2 obtained in Reference Example 6. The physical properties and characteristics of the obtained film are shown in Table 1.

[0088] Example 3 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except for using MB3 obtained in Reference Example 7. The physical properties and characteristics of the obtained film are shown in Table 1.

[0089] Example 4 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that no cooling after the annealing treatment was performed and the winding temperature was set at the temperature shown in Table 1. The physical properties and characteristics of the obtained film are shown in Table 1.

[0090] (Examples 5 to 6) A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that the annealing temperature was changed to the conditions shown in Table 1. The physical properties and characteristics of the obtained film are shown in Table 1.

[0091] Example 7 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that the heat setting temperature was changed to the conditions shown in Table 1. The physical properties and characteristics of the obtained film are shown in Table 1.

[0092] Example 8 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction of the film was 2.0 times and the stretching ratio in the width direction of the film was 2.5 times. The physical properties and characteristics of the obtained film are shown in Table 1.

[0093] Example 9 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that 100 parts by mass of PPS1 obtained in Reference Example 1 was used to form a film. The physical properties and characteristics of the obtained film are shown in Table 1. Example 10 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that the annealing temperature was changed to the conditions shown in Table 1. The physical properties and characteristics of the obtained film are shown in Table 1. Example 11 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that the heat setting temperature was changed to the conditions shown in Table 1. The physical properties and characteristics of the obtained film are shown in Table 1.

[0094] Comparative Example 1 Except for not carrying out the annealing treatment, a biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1. The physical properties and characteristics of the obtained film are shown in Table 1.

[0095] Comparative Example 2 A 50 μm-thick unstretched film was produced at a casting drum speed of 30 m / min. The film was heat-treated under the conditions shown in Table 1 to obtain a polyarylene sulfide film. The sample obtained was highly crystalline and could not be processed.

[0096] Comparative Example 3 A biaxially oriented polyarylene sulfide film was obtained in the same manner as in Example 1, except that the annealing temperature was changed to the conditions shown in Table 1. The physical properties and characteristics of the obtained film are shown in Table 1.

[0097] [Table 1A]

[0098] [Table 1B]

Claims

1. A biaxially oriented polyarylene sulfide film containing a polyarylene sulfide resin as a main component, the melting initiation temperature (Tms) and melting point (Tm) measured in the first run using differential scanning calorimetry (DSC) at a heating rate of 20° C. / min and a sample weight of 5 mg satisfy the following formula (1), and the rigid amorphous content of the entire film is 40% or more and 55% or less. 20°C ≦ Tm - Tms ≦ 100°C (1)

2. A biaxially oriented polyarylene sulfide film comprising a polyarylene sulfide resin as a main component, the melting start temperature (Tms) and melting point (Tm) measured in the first run using differential scanning calorimetry (DSC) at a heating rate of 20°C / min and a sample weight of 5 mg satisfy the following formula (1), and the proportion of rigid amorphous content in the entire film is greater than the degree of crystallinity. 20°C ≦ Tm - Tms ≦ 100°C (1)

3. 3. The biaxially oriented polyarylene sulfide film according to claim 1, wherein the rigid amorphous content is 40% or more and 55% or less of the entire film, and the ratio of the rigid amorphous content is greater than the degree of crystallinity.

4. 3. The biaxially oriented polyarylene sulfide film according to claim 1, characterized in that the onset temperature of shrinkage stress measured by thermomechanical analysis (TMA) is 220° C. or higher.

5. 3. The biaxially oriented polyarylene sulfide film according to claim 1, wherein the shrinkage stress at 250° C. is 3.0 MPa or less.

6. A biaxially oriented polyarylene sulfide film according to any one of claims 1 to 5, comprising a PAS-based resin (I) as a main component and at least one thermoplastic resin (II) different from the resin (I), wherein the thermoplastic resin (II) has any one of the following skeletons: 【Chemistry 1】 (However, R in the formula 1 ~R 6 are each any one of hydrogen, a hydroxyl group, a methoxy group, an ethoxy group, a trifluoromethyl group, an aliphatic group having 1 to 13 carbon atoms, and an aromatic group having 6 to 10 carbon atoms.

7. 7. The biaxially oriented polyarylene sulfide film according to claim 6, characterized in that the resin (II) has a sulfonyl group.

8. 8. The biaxially oriented polyarylene sulfide film according to claim 1, wherein at least one of the surfaces has a center surface average roughness (SRa) of 15 nm or more and 300 nm or less.

9. 9. The biaxially oriented polyarylene sulfide film according to any one of claims 1 to 8, characterized in that the average value (Q) of the orientation parameter measured by a molecular orientation meter is 4,300 or more.

10. A composite of the film according to any one of claims 1 to 9 and at least one of a metal film, a resin film and a fiber sheet.

11. A circuit member using the film according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Biaxially oriented polyphenylene sulfide film

    JP1994322151A

  • Thermal adherence of polyphenylene sulfide resin to fluorine resin

    JP1996103955A

  • Polyphenylene sulfide film and capacitor

    JP2001329076A

  • Polyphenylene sulfide film and method of preparing the same and circuit board produced from the same

    JP2002047360A

  • Polyphenylenesulfide film for circuit board

    JP2004096040A